I am doing equivalent logarithms and would like to know how to simplify the following log(x^2)-log(x) Nov 11 | Heather from Fort Lauderdale, FL | 3 Answers | 0 Votes Mark favorite Subscribe Comment
I don't see any reason to vote down. Based on the properties of the logarithmic function, there are few ways to solve this problem (or notations to write the solution). log x^{2} - log x = 2log x - log x = log x Nov 12 | Nataliya D. Comment
For the moment, think of log(x^2) as being log(x*x) We know from the rules of logarithms that log (x*y) = log(x) + log(y) In this case, log(x^2)-log(x) = log(x) + log(x) - log(x) = log(x) Nov 11 | William S. Comment